Dr. Nur Farhayu produces lightweight concrete panels from coal waste - Safriza, Baharuddin; Nur Hartini, Mohd Hatta (2020)
15 September 2020 - A researcher of the Faculty of Civil Engineering Technology (FTKA), Universiti Malaysia Pahang (UMP), Dr. Nur Farhayu Ariffin, 33, has used 100% waste from coal power plants to produce lightweight concrete panels.